Avaliação de diferentes métodos matemáticos para validar exigências de lisina, treonina e metionina+cistina digestíveis para matrizes pesadas - Oliveira, Cleber Franklin Santos de (2013)
The objective of this study was to evaluate different mathematical methods to validate requirements lysine, threonine and methionine plus cystine for broiler breeders. To validate the nutritional recommendations of each amino acid were proposed two different methods based on dose response (polynomial and broken line) and factorial. The experimental design was completely randomized with seven treatments with six replicates of ten birds per pen for lysine, four replicates with ten birds per pen for threonine and seven replicates with one bird per cage for methionine and cystine. The eighth treatment was only included to verify if amino acid in the first study were as limiting in diets. The treatments were obtained by dilution technique. The experiment lasted ten weeks, where the first six were for adaptation to the diets of birds and the last four for the data collected. From the answers the intake of amino acids, estimated the mass coefficient of eggs by the Reading model to meet the proposed factorial design: Amino acid (mg / bird / day) = (a.MO) + (b.PBm0, 73.u) + (0,18.PP.z). For lysine was no significant effect (P <0.05) for feed intake, production, weight and egg mass, mass conversion and per dozen eggs. Threonine was no significant effect (P <0.05) for feed intake, production, weight and egg mass, mass conversion and per dozen eggs. For methionine and cystine was no significant effect (p <0.05) for feed intake, egg production, egg weight, egg mass, mass conversion and per dozen eggs. The requirements for the different regression models, broken line, Quad∩BL and factor were to lysine 815, 564, 649 and 449mg / day respectively bird, threonine 343, 594, 439 and 694mg / day respectively bird and methionine plus cystine 471 , 678, 571 and 673mg / bird / day, respectively.